E. coli-expressed SECRET AGENT O-GlcNAc modifies threonine 829 of GIGANTEA - Kim, Young-Cheon; Hartweck, Lynn M.; Olszewski, Neil E. (Frontiers in Plant Science, 2024)
The Arabidopsis thaliana glycosyl transferases SPINDLY (SPY) and SECRET AGENT (SEC) modify nuclear and cytosolic proteins with O-linked fucose or O-linked N-acetylglucosamine (O-GlcNAc), respectively. O-fucose and O-GlcNAc modifications can occur at the same sites. SPY interacts physically and genetically with GIGANTEA (GI), suggesting that it could be modified by both enzymes. Previously, we found that, when co-expressed in Escherichia coli, SEC modifies GI; however, the modification site was not determined. By analyzing the overlapping sub-fragments of GI, we identified a region that was modified by SEC in E. coli. Modification was undetectable when threonine 829 (T829) was mutated to alanine, while the T834A and T837A mutations reduced the modification, suggesting that T829 was the primary or the only modification site. Mapping using mass spectrometry detected only the modification of T829. Previous studies have shown that the positions modified by SEC in E. coli are modified in planta, suggesting that T829 is O-GlcNAc modified in planta.